(untitled) (The Review of Diabetic Studies, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality worldwide, characterized by progressive airflow limitation, dyspnea, and reduced exercise capacity. Multidisciplinary care models that integrate physical therapy and nursing interventions are increasingly recognized as essential to optimizing outcomes in COPD management. Objective: This systematic review aimed to evaluate the impact of integrating physical therapy and nursing care on dyspnea severity and exercise capacity in patients with COPD. Methods: A comprehensive search was conducted across PubMed, Scopus, Web of Science, CINAHL, and Cochrane Library databases for studies published between 2005 and 2025. Eligible studies included randomized controlled trials, quasi-experimental studies, and cohort studies that examined combined physical therapy and nursing interventions in COPD patients. Primary outcomes were dyspnea (measured by the Modified Medical Research Council [mMRC] scale or Borg scale) and exercise capacity (measured by the 6-Minute Walk Test [6MWT] or other validated tests). Studies were screened, data extracted, and quality assessed using the Cochrane risk-of-bias tool. Results: Twelve studies involving 1,248 COPD patients met inclusion criteria. Integrated care programs demonstrated significant improvements in dyspnea reduction and exercise tolerance compared to standard care. Physical therapy components such as pulmonary rehabilitation, breathing exercises, and endurance training combined with nursing-led interventions including patient education, medication adherence support, and symptom monitoring yielded synergistic benefits. Pooled data revealed a mean improvement of 45 meters in 6MWT distance and a reduction in dyspnea scores by 1–2 points on validated scales. Conclusion: The integration of physical therapy and nursing care enhances COPD management by improving dyspnea and exercise capacity, thereby promoting functional independence and quality of life. Systematic implementation of multidisciplinary interventions is recommended in routine COPD care pathways. Further high-quality trials are warranted to establish standardized protocols and assess long-term outcomes.